Templated growth formation of mesoporous silica materials: a soft-hard template approach - Reva Edra Nugraha; Nur Aini Fauziyah; Guardiola Rosa Wira (Nusantara Science and Technology Proceedings, 2022)
Mesoporous silica is continuously raising in popularity due to its excellent and unique properties, such as customizable pore, surface shape/morphology, large pore volume, and ease of functionalization for wide applications like catalysis, energy, environment, and biomedical areas. In the templated growth synthesis, a template acts as a mesostructure-directing agent to produce hollow porous structures in silica frameworks. Templates can be divided into "hard" and "soft" templates. While soft templates are typically in a fluid-like condition and hard templates are typically solid-state materials with specific morphology and structure. In this minireview, we summarize the synthesis method of mesoporous silica with a soft-hard template approach (template-assisted method).